Pendekatan Dosen Dalam Pembinaan Akhlak Mahasiswa Di Institut Parahikma Indonesia (IPI) Gowa - Nurhikmah (el-Idarah: Jurnal Manajemen Pendidikan Islam, 2018)
This study discussed about "Lecturer Approach to the Students Moral Development at Parahikma Institute of Indonesia". The type of research used was descriptive qualitative research. The objective of the research was to find out the lecturers’ approach. The subjects of the study were 8 (eight) lecturers at Parahikma Institute of Indonesia (IPI). In this study, the author applied descriptive qualitative management techniques with inductive data analysis. The data was obtained through observation, interview, and documentation. It was found from the research on the lecturers approach at Parahikma Institute of Indonesia, namely; educational approach, functional approach, and emotional approach. The forms of approach implementation conducted by the lecturers at IPI, such as tilawah approach (teaching), tazkiyah approach (purification), exemplary approach, and the results of the lecturer approach in the guidance of morality of students who are in the campus environment always applied exemplary attitude towards the prophet p.u.b., the lecturers and colleagues. They always prayed before and after learning activities, greeted, got used to praying together in the mosque. They were also active in the celebrations of Islamic holiday, accustomed to forgiveness, discipline, and boosted honesty